Sweeter together? Assessing the combined influence of product‐related and contextual factors on perceived sweetness of fruit beverages. Issue 3 (22nd February 2019) - Wang, Qian Janice; Mielby, Line Ahm; Thybo, Anette Kistrup; Bertelsen, Anne Sjørup; Kidmose, Ulla; Spence, Charles; Byrne, Derek Victor
Abstract: It is well‐known that multiple sensory cues influence flavor perception and liking. The present study aimed to combine and compare the relative influences of product‐related and contextual factors on taste perception and liking, with a focus on the perception of sweetness. Participants tasted samples of the same base fruit beverage with one of three different levels of added aroma, while the contextual cues (either visual or auditory) were displayed simultaneously using iPads. The results revealed that both added aroma and background music significantly influenced participants' sweetness ratings, with a medium level of added aroma enhancing sweetness significantly as compared to no added aroma, and with the sweet‐congruent soundtrack enhancing perceived sweetness significantly as compared to the bitter‐congruent soundtrack. Moreover, there was a potentially additive effect from the combination of aroma and soundtrack. These results are discussed in terms of potential mechanisms underlying multisensory flavor perception. Practical applications: Consumers are nearly always exposed to a multisensory environment whenever they consume food and drink. It is therefore important to acknowledge that, beyond the food itself, what people happen to be exposed to in the environment while eating or drinking can influence their multisensory flavor experiences as well. These results are of relevance for those working on understanding a theoretical model of human sweetness perception, as well as those working on the design of healthier, sugar‐reduced food products. Indeed, the knowledge that multiple sensory cues can, at least under the appropriate conditions, work in conjunction to deliver a greater modulation of perceived taste will allow designers to come up with more effective sugar‐reduced products without reducing consumer satisfaction. Moreover, the increasing prevalence of sensory and augmented reality applications means that manufacturers can now incorporate external visual and auditory content as part of the total multisensory product experience.